The Significance of Students' Independent Work in Learning Activities (Eurasian Journal of Learning and Academic Teaching, 2022)
The student's independent work, in the general context of his self-education, is the highest form of his educational activity according to the criterion of self-regulation and goal-setting; it can be differentiated depending on the source of control, the nature of motives, etc.